PRODUÇÃO DE ÁLCOOL A PARTIR DE BATATA-DOCE COM VARIAÇÕES NAS CONDIÇÕES DE FERMENTAÇÃO - Santos, Eveline Gheller dos (2015)
One of the major environmental issues facing the planet has been the drastic increase in the emission of CO2 (carbon dioxide) in the atmosphere, causing many investments in the environmental research for to control and/or minimize the damages caused by these emissions. Given the importance of ethanol as a way to minimize the amount of CO2 emitted around the world, this study aims to produce ethanol from sweet potato flour, varying reaction conditions for fermentation, such as pH, temperature and time. The raw material was characterized from the moisture, reducing sugars and starch, and its values in percentages were 4.13, 4.04 and 71.80, respectively. In order to check the best process for achieving high alcohol levels, experiments were performed hydrolysis of acid and enzymatic type. The distillate samples showed that the higher alcohol percentages were made from acid hydrolysis, being 26.42% the maximum alcohol percentage obtained. In relation to the distillate samples made from enzymatic hydrolysis, the higher alcohol percentage was found to be 25.04%. For both samples with high alcohol content, fermentations were performed at pH 5.0 and 36ºC, during a period of five days. The fermentation time was the most important variable, with higher significance values for both types of hydrolysis used in this study.